Cold wallet [videorecording (DVD)] - Hibey, John; Castillo, Raúl; Diaz, Melonie; Cavalero, Tony, 1983- (Well Go USA Entertainment, 2025)
After losing everything in a cryptocurrency scam, a ragtag team of vigilante Redditors attempt to kidnap the kingpin who screwed them over. But when the home invasion takes a turn for the worse, they become victims in a sadistic game.